Penegakan Hukum terhadap Penyalahgunaan Narkotika - Made Ratih Pradnyantari; I Gusti Bagus Suryawan; I Nyoman Sujana (Warmadewa Press, 2021)
Narcotics misappropriations have the bad impacts for nation generation continuance. The anticipation needs cooperation from all society elements, such as family, every education stages until universities and government must be united on narcotic. Prevention efforts in environment around them. The aims of this research are as follows: 1. To find out the steps which are applied by low enforcement in against narcotics misappropriation, 2. To find out and understand about doubt imposition which is did by the users of narcotics misappropriation. The law object source of this research is primary and secondary law object, the technique of accumulating is using document regristration method and recite the law regulations which are related to the problem and analysis by using descriptive qualitative.From the result of observation and researsech, the step that all of society element in narcotic prevention efforts in society environment, such as: 1. Promotive method, 2. Presentative method, 3. Repressive method, 4. Curative method, 5. Rehabilation. Criminal doubt is given for the narcotics addict who is walk on punishment period in jail, where as the action doubt is given for narcotics addict who become as a victim. Therapy and treatment will held as the rehabilition facilities.Government as policy taker is expected can formulate laws and regulations which are more binding in controlling and production of narcotics in Indonesia, and there is needs socialiscation and eludication about the impact of narcotics misappropriation.